Cryptococcus neoformans Induces MCP-1 Release and Delays the Death of Human Mast Cells - Lopes, José Pedro; Stylianou, Marios; Backman, Emelie; Holmberg, Sandra; Ekoff, Maria; Nilsson, Gunnar; Urban, Constantin F. (Frontiers in Cellular and Infection Microbiology, 2019)
Cryptococcosis, caused by the basidiomycete Cryptococcus neoformans, is a life-threatening disease affecting approximately one million people per year worldwide. Infection can occur when C. neoformans cells are inhaled by immunocompromised people. In order to establish infection, the yeast must bypass recognition and clearance by immune cells guarding the tissue. Using in vitro infections, we characterized the role of mast cells (MCs) in cryptococcosis. We found that MCs recognize C. neoformans and release inflammatory mediators such as tryptase and cytokines. From the latter group mainly CCL-2/MCP-1, a strong chemoattractant for monocytic cells. We demonstrated that supernatants of infected MCs recruit monocytes but not neutrophils. During infection with C. neoformans, MCs have a limited ability to kill the yeast depending on the serotype. C. neoformans, in turn, modulate the lifespan of MCs both the presence of its polysaccharide capsule and by secreting soluble modulators. Taken together, MCs might have important contributions to fungal clearance during early stages of cryptocococis where these cells regulate recruitment of monocytes to mucosal tissues.